Management of dermatoses with topical clobetasol propionate 0.025% - Gopala, Maragondanahalli G.; Warad, Sidramappa R.; Puhan, Manas R.; Agrawal, Saurabh; Parbhani, Sanjay J.; Mehendiratta, Kavita; Gupta, Mahaveer P.; Taj, Farhana T.; Chirag, Vamja; A., Satish D. (International Journal of Research in Medical Sciences, 2022)
The development of topical corticosteroids (TC) has enabled effective treatment of many dermatoses. The main therapeutic activity of topical corticosteroids is their nonspecific anti-inflammatory effect that primarily seems to be a result of their action on the chemical mediators of inflammation. Topical corticosteroids have also been shown to be antimitotic. Corticosteroids also play a vital role in cellular signaling, immune function and protein regulation. Clobetasol propionate (CP) 0.025% is a prescription corticosteroid medicine, used to treat moderate to severe plaque psoriasis in patients 18 years of age and older. It is a class I specialized cream formulation, that is free of propylene glycol, short-chain alcohols (e.g. ethanol), and sorbitan sesquioleate, a sorbitol-based emulsifier which is a common contact allergen used in many topical corticosteroid formulations. This case series discusses about management of different dermatoses using ImpoyzTM (clobetasol propionate) cream 0.025%.